Exploring the Relationship between Social Class and Quality of Life: the Mediating Role of Power and Status - Wingen, Tobias; Englich, Birte; Estal-Muñoz, Víctor; Mareva, Silvana; Kassianos, Angelos P. (My University, 2021)
Why does social class affect Quality of Life? We simultaneously investigated two novel possible explanations: Because a high social class is associated with increased control over resources (i.e., power) or because a high social class is associated with higher respect and esteem in the eyes of others (i.e., status). To test these explanations, we collected data from 384 US-based individuals. We measured their social class, power, status, and four facets of Quality of Life (physical, mental, social, and environmental). For each facet, we calculated the correlation with social class. Next, we tested whether the relationship between social class and the specific facet was mediated by power, status, or both. Social class correlated significantly with all facets of Quality of Life (physical, mental, social, and environmental). Using parallel mediation models, we found that this positive relationship was mediated by status, but not by power. For some facets of Quality of Life (physical, environmental), power even had a negative indirect effect. These results suggest that upper-class individuals indeed have a higher Quality of Life. However, this seems to be mostly due to the increased status of upper-class individuals, whereas power was less important or even had detrimental effects on Quality of Life. Researchers and policymakers aiming to address class-based Quality of Life inequality could thus benefit from focusing on status as an important mediator. Moreover, our work demonstrates the importance of considering power and status as distinct constructs, in order to fully unravel the relationship between social class and Quality of Life.
Keywords: Inequality; Quality of life; Social class; Status; Power